PENGARUH CITRA MEREK, KESADARAN MEREK, DAN KUALITAS PRODUK TERHADAP KEPUTUSAN MEMBELI PRODUK APPLE - Surya Adi Dharma, Ngakan Putu; Sukaatmadja, I Putu Gde (E-Jurnal Manajemen; Vol 4 No 10 (2015), 2015)
Globalization has affected in the economic matters, where consumer decision becomes more complicate selecting or purchasing competitive brands in the global market place. The study aims to determine the effect of brand image, brand awareness, and product quality against the purchase decision of Apple products in Denpasar city. The sample size used by 112 respondents, with a non-probability sampling method, especially purposive sampling. Analysis technique was using are multiple regression. The results of this study showed these independent variables are brand image, brand awareness, and product quality has a positive and significant effect with the purchase decision of Apple products in Denpasar city. The study suggests that the management and marketing department of the Apple manufacturer, especially Apple reseller in Denpasar city to inform these research to the Apple manufacturer in order to maintain brand image, brand awareness, quality products that will influence the consumer's decision to buy Apple products.Apple manufacturer ought to maintain brand image, brand awareness and product quality which will influence the consumer’s decision to purchasing Apple products.
Keywords: brand image, brand awareness, product quality, purchase decision.